Identifikasi Density Figure dan Pengendalian Vektor Demam Berdarah pada Kelurahan Karanganyar Gunung (Universitas Negeri Semarang, 2022)
Dengue Hemorrhagic Fever (DHF) is a disease that has a main vector of the Aedes aegypti mosquito by transmitting the disease through its bite. Based on 2018 Health Department data, Semarang Larva Free Index (LFI) in 2018 was 91.7%. To find out the population density of Aedes aegypti larvae in the densely populated Karanganyar Gunung Village, a study was conducted. Based on the analysis of research data, the value of Larva Free Index (LFI) = 94.77%, House Index (HI) = 5.22%, Container Index (CI) = 2.86% and Breteau Index (BI) = 5.72%. So that from value of HI, CI and BI, value of Density Figure (DF) obtained is two. This shows that the larvae density is moderate. So that action is needed to control mosquitoes as a vector of dengue fever. From the results of the questionnaire, physical vector control was 92% of the total 105 respondents. While chemical control (such as using mosquito coils) was carried out by 90%, biology (such as keeping fish in water reservoirs for mosquito larva predators) by 61% and self-protection (such as using of anti-mosquito lotions) by 46% of a total of 105 respondents. However, there are still 2% of the total 105 respondents who did not control the vector at all.